Chemical and spectroscopic studies of the capsular polysaccharides of some klebsiella and escherichia coli serotypes - Stanley, Shawn Mark Ross (Rhodes University, Faculty of Pharmacy, Pharmacy, 1990)
The work described in this thesis forms part of an international programme concerned with the structure elucidation of the capsular antigens of some Enterobacteriaceae. Many of the Klebsiella and some of the Escherichia coli are pathogenic to man and, hence, they are of interest. The virulence of bacteria is a multifactorial phenomenon, in which characteristic traits of bacteria and their hosts play comparable and complementary roles. It is accepted that pathogens are more virulent when encapsulated, because, nearly all disease causing bacteria have a capsule when freshly isolated from the host. This increase in pathogenicity is related, in part, to the capsular polysaccharides' ability to avoid or attenuate the host defence mechanisms. In the majority of cases the protective aspects of the capsule are overcome in the latter stages of infection when the formation of specific antibodies by the host has occurred. However there are situations in which an immune state of the infected host is virtually never reached, and susceptiblity to the infecting bacteria is maintained even in the advanced stage of an infection. Explanation of this phenomenon becomes possible by analysing the structure of the polysaccharides. The inability of the host to raise an immune response to the capsule may be because the structure of the polysaccharide is similar or identical to the host's carbohydrates. The serological and pathogenic relatedness of encapsulated E. coli and Klebsiella, to the encapsulated strains of other genera, is based on structural identity or similarity of the respective capsules. Capsular polysaccharides are analysed by both chemical and instrumental methods, and, at present, nuclear magnetic resonance spectroscopy is the most important analytical technique
Keywords: Polysaccharides; Klebsiella; Escherichia